37.1k views
2 votes
Prove that Sec^2xcot^2x-cos^2xcsc^2x=1

User Jkovba
by
5.2k points

1 Answer

2 votes

Answer:

see explanation

Explanation:

Using the trigonometric identities

• sec x =
(1)/(cosx), csc x =
(1)/(sinx)

• cot x =
(cosx)/(sinx)

Consider the left side

sec²x. cot²x - cos²x. csc²x

=
(1)/(cos^2x) ×
(cos^2x)/(sin^2x) - cos²x ×
(1)/(sin^2x)

=
(1)/(sin^2x) -
(cos^2x)/(sin^2x)

=
(1-cos^2x)/(sin^2x)

=
(sin^2x)/(sin^2x) = 1 = right side ⇒ proven

User Jackdbernier
by
5.7k points